Magnetic ring array with high-amplitude negative stiffness for high performance micro-vibration isolation. (June 2023) - Zhao, Yamin; Cui, Junning; Zou, Limin
A magnetic ring array (MRA) with high-amplitude negative stiffness is proposed to counteract the positive stiffness of vibration isolators and improve the low-frequency performance of heavy-load precision micro-vibration isolation. The MRA uses magnetic rings mounted coaxially and magnetized perpendicularly to form an array structure that produces high-amplitude negative stiffness. An analytical model of its magnetic force and stiffness is established, and the influence of geometric parameters on stiffness is analyzed for optimization. Furthermore, the effectiveness of the MRA is validated through comparisons with existing schemes. A set of experiments are carried out to prove the validity of the analytical model and the performance of the MRA. Experimental results show that the natural frequency of the vibration isolation experimental setup decreases from 4.75 Hz to 1.13 Hz after the introduction of the MRA, and the peak of the one-third octave band velocity spectra decreases from 5.03 μm/s @ 5 Hz to 2.60 μm/s @ 1.25 Hz. The effectiveness of the proposed MRA in improving the performance of micro-vibration isolation is verified. Graphical Abstract